2003
DOI: 10.1002/bit.10581
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibody binding to three cancer‐related antigens using flow cytometry and cell tracking velocimetry

Abstract: Proper antibody labeling is a fundamental step in the positive selection/isolation of rare cancer cells using immunomagnetic cell separation technology. Using either a two-step or single-step labeling protocol, we examined a combination of six different antibodies specific for three different antigens (epithelial specific antigen, epithelial membrane antigen, and HER-2/Neu) on two different breast cancer cell lines (HCC1954 and MCF-7). When a two-step labeling protocol was used (i.e., anti-surface marker-fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…In addition, it was observed that the magnetophoretic mobility of immunomagnetically labeled cells is a saturation type function of the concentration of the antibody-nanoparticle conjugates used to label the cells (Chosy et al, 2003;Comella et al, 2001). While a saturation type relationship is theoretically expected, based on typical antibody-antigen interactions, the scale-up of immunomagnetic cell separations for clinical applications may require a considerable amount of antibody which can be financially limiting.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, it was observed that the magnetophoretic mobility of immunomagnetically labeled cells is a saturation type function of the concentration of the antibody-nanoparticle conjugates used to label the cells (Chosy et al, 2003;Comella et al, 2001). While a saturation type relationship is theoretically expected, based on typical antibody-antigen interactions, the scale-up of immunomagnetic cell separations for clinical applications may require a considerable amount of antibody which can be financially limiting.…”
Section: Introductionmentioning
confidence: 96%
“…While a saturation type relationship is theoretically expected, based on typical antibody-antigen interactions, the scale-up of immunomagnetic cell separations for clinical applications may require a considerable amount of antibody which can be financially limiting. Significant experimental evidence has demonstrated that the performance of both the commercial MACS systems as well as the flow through technology being developed in our laboratories is a clear function of the magnetophoretic mobility of the labeled cell (Chosy et al, 2003;Comella et al, 2001;McCloskey et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Particle Tracking Velocimetry (PTV) and magnetophoresis of immunomagnetically labeled cells was combined by Zborowski et al [35][36][37][38][39][40][41] They measured the magnetophoretic velocity of an individual labeled cell under an inhomogeneous magnetic field, and then the magnetophoretic mobility was determined. In their theoretical treatment, the magnetophoretic mobility depended on the number of magnetic labels.…”
Section: ·3 Microparticle Analysis By Magnetophoretic Velocimetrymentioning
confidence: 99%
“…Antibody Binding Capacity (ABC) was defined as the quantity representing how many magnetic nanoparticles could bind per single cell, and the difference of ABC between individual cells was investigated. 41 The magnetophoretic velocity of a macrophagic cell, which was fed by the magnetic nanoparticle, was investigated and the number of nanoparticles uptaken was determined quantitatively by Wilhelm and co-workers. 42 The number of magnetic particles in the cell was determined by the ferromagnetic resonance as well.…”
Section: ·3 Microparticle Analysis By Magnetophoretic Velocimetrymentioning
confidence: 99%
“…The nanoparticles are fixed to the cell via the attachment of antibodies to the specific antigens on the cell's surface (Chosy et al 2003). The Stokes viscous drag on the spherical cell is given by…”
Section: Cells Decorated With Nanoparticlesmentioning
confidence: 99%